Phase noise reduction in a CMOS LC cross coupled oscillator using a novel tail current noise second harmonic filtering technique. (July 2017) - Jafari, Bahram; Sheikhaei, Samad
Abstract: A novel technique for reducing phase noise of LC cross coupled oscillators is proposed, using second harmonic filtering of the tail current noise. Using a LC network in between tail current and switching transistors, second harmonic of the tail current noise is filtered out. The filtering circuit works simultaneously as low pass and band stop filters. Therefore, output phase noise is reduced. Three circuits including basic cross coupled oscillator with tail current, and two cross coupled oscillators with conventional and proposed method of tail current noise second harmonic filtering are designed and simulated in 0.13 µm CMOS technology, with the same power consumption from 1.2 V supply. Simulation results show that for the proposed circuit, at 2 GHz frequency and 1 MHz offset, phase noise and Figure of Merit (FoM) are −130dBc/Hz and 192.3 dB, respectively. Compared to basic and conventional circuits, proposed method presents phase noise improvements of 13 dB and 7.5 dB, respectively, at the cost of increased die area, due to the filtering inductor. Graphical abstract: